Online Job Search: A Study on Optimizing Online Platforms to Facilitate Effective Job Search - Jayawardana, S.U.; D.R. Bamunuge; Wijethunga, A.M.D.K.S.; Abeygoonawardana, G.A.C.I.; De Silva, D.I.; Dias, S. M. D. T. H. (International Journal of Engineering and Management Research, 2022)
Technological advancement along with the expanding number of users and internet-based businesses have created a worldwide market for both job recruiters and job seekers. This has drastically changed areas of job searching and job recruiting. Traditional methods of recruiting and job hunting have been obsoleting since the introduction of digitalized platforms to perform these tasks, leading to better results when matching the intents of job recruiters to job seekers. There are numerous online job search platforms but everyone one of them contains some major issues. We have examined the related studies and identified that these issues exist in the areas of screening job applications, optimizing job search queries, and demographic inequity in candidate selection. Although these topics have been researched independently, there is a lack of implementational solutions available to address all these issues together. As a result of our study on this deficiency, we have come up with a practical solution implemented as a web application addressing these issues and providing job seekers and job recruiters with an online platform with enhanced accuracy and user experience.